The M|D|oo queue busy cycle distribution - Ferreira, M. A. M. (2014)
Given the busy period major importance in queuing systems, it is also relevant to study the busy cycle. In this work some interesting results on M|G|? queue system busy cycle distribution are presented. They are emphasized for the M|D|? queue system and a numerical method to compute the M|D|? queue system busy cycle distribution function is presented.